DVB Coverage Prediction Using Game Engine Based Ray-Tracing Techniques (2011)
This paper presents the results of an evaluation of a propagation model based on ray-tracing techniques using a game engine and Graphics Processing Unit (GPU) in outdoor scenarios, as a gap-filler for a Digital Video Broadcasting Handheld (DVB-H) service. This model involves complete identification of the parameters of wave propagation, multipath components between the transmitter and the receiver as attenuation, time delay of arrival (TDA), full polarimetric transmission matrix, direction of arrival DoA and the direction of departure DoD. In the paper, we present the results of the simulation and compare them with measurements, obtaining a satisfactory fit. © 2011 IEEE.